Factors associated with telemedicine use in a tertiary care pediatrics center - A cross-sectional study - A.S. Irfanahemad; B.S. Nandakumar; A.P. Ugargol; K. Radhika (Al Ameen Medical College, 2018)
Introduction: While quality health-care is considered a fundamental human right for all citizens; the challenge remains in making it accessible to all. Information systems have been identified as possible solution that can be used to alleviate disparity between rural and urban healthcare services and bridge the digital divide. Literature has suggested that one of the barriers for successful implementation of health information system is the user acceptance by health care personnel. Objectives: To assess the factors associated with telemedicine use in a tertiary care pediatric center. Method: This is a cross-sectional study, using mixed methods to obtain data from a sample of research participants from tertiary care pediatrics center during July to October 2017. Results: In general the health-care personnel were aware of the benefit of tele-medicine to improve effectiveness and efficiency of the health care system. The barriers to the effective implementation of tele-medicine include lack of knowledge and lack of awareness regarding use and usage of the tele-medicine system. Conclusion: Health care personnel do acknowledge that tele-medicine can help to increase the effectiveness of the healthcare system. In general the acceptance of tele-medicine among healthcare personnel is positive. However in order to integrate it into standard work practices, specific training and capacity building for tele services is essential among health care personnel.